Survei Sarana Dan Prasarana Pendidikan Jasmani Sekolah Dasar Di Kecamatan Winong Kabupaten Pati Tahun 2021 (Indonesian Journal for Physical Education and Sport, 2021)
Arif Rahman,. 2021. Survey of Physical Education Facilities and Infrastructure Elementary School in Winong Sub-District Pati Regency. A Final Project. Physical Education, Health and Recreation, Faculty of Sport Sciences, Universitas Negeri Semarang. Advisor: Roas Irsyada S.pd.,M.pd. Keywords: Physical Education, survey, facilities, infrastructure. The background of this research is based on preliminary observation indicates that there is need for data about the availability and condition of facilities and infrastructure to support physical education learning in Kedu Sub-District Elementary School, Temanggung Regency. The purpose of this research is to know the results conditions of physical education learning facilities and infrastructure at the elementary school in Kedu Sub-District Temanggung Regency. The research method used is a survey with a quantitative descriptive approach. The research site is located in Temanggung Regency with a research target of 10 elementary schools in Winong Sub-district Pati Regency. Data collection techniques using quota sampling techniques. Instruments used using observations, interviews with Principals and Physical Education Teachers, observation sheets and documentation. Data collection includes the number of tools, the number of tools, the number of facilities, the condition of the tool, the condition of the tool and the condition of the facility. The analysis used is quantitative descriptive by classifying the types of data obtained from observation sheets and grouped. Based on the data analysis that has been carried out in the Survey of Physical Education Facilities and Infrastructure in Public Elementary Schools in Winong District, Pati Regency, it can be concluded that the results of the study on the condition of the number of physical education learning facilities and infrastructure in Public and Private Elementary Schools in Winong District, Pati Regency from 10 It is known that all elementary schools are in the Enough category (100%). Then the condition of the number of Physical Education learning tools in the State Elementary School, Winong District, Pati Regency, out of 10 elementary schools it is known that there are 2 schools in the good category (20%), there are 8 elementary schools that fall into the sufficient category (80%) and 0 schools are in the good category. less ( 0% ). This research concludes that the facilities and infrastructures in elementary school in Winong sub-district Pati Regency are in medium category. The suggestion given by researchers is for the Pati Regency government to more attention to the facilities and infrastructure available at the elementary school in Winong sub-district and physical education teachers can support and modify the facilities and infrastructure available at the school especially in Public and Private Elementary Schools in the Winong District, Pati Regency.